Intensifying rice (Oryza sativa) based cropping system through pulses and oilseeds in North-East India - LAYEK, JAYANTA; DAS, ANUP; R, KRISHNAPPA; I, RAMKRUSHNA G; CHOWDHURY, SAMIK; DAS, SANTANU (The Indian Journal of Agricultural Sciences, 2021)
Cultivation of pulses and oilseeds in north eastern region (NER) of India assumes greater significance in view of high deficits in production for nutritional security. A field experiment was conducted for two consecutive years 2013-14 and 2014-15 to study the possibility of growing three crops in a year in the valley land rice (Oryza sativa L) ecosystem by following conservation tillage and cultivation of short duration pulses/oilseed crops and to study their impact on system productivity, water use efficiency, net return and soil fertility. While, the average rice yield (4.78 t/ ha) was significantly higher under the rice-pea-greengram system, the system rice equivalent yield (13.61 t/ha) was the maximum under rice-pea-French bean followed by (12.55 t/ha) rice-pea-blackgram as compared to rice-fallow (4.64 t/ha) systems. Higher cultivated land utilization index was recorded under rice-lentil-greengram (0.97) and rice-lentilblackgram (0.93) than other systems. The highest net returns were realized under rice-pea-French bean (₹ 118392/ ha) followed by rice-pea-black gram system (₹ 110267/ha) over a low net returns (₹ 39040/ha) from rice-fallow. The soil organic carbon, available N and soil microbial properties were substantially enhanced due to inclusion of legumes in rice based system and the highest value of these properties were evident under rice-pea-greengram followed by rice-pea-blackgram systems. Thus, inclusion of short duration legumes like lentil and pea in winter season and green gram, blackgram or French bean in summer season under conservation tillage can enhance the cropping intensity to 300%, improve soil health and enhance system productivity and income by two to three times in NER.